Examining the effect of employment on delinquency: a longitudinal study of South Korean youths - Lee, Hee-Jung (Crime & delinquency, 2017)
This study focuses on examining the effects of employment and work hours on delinquency during adolescence. Juvenile employment and work hours are hypothesized to increase delinquency, and the longitudinal panel data obtained from the Korean Youth Panel Survey are utilized. Results from fixed effects models showed that working youths are more likely to participate in crime, substance use, and status offenses. Regarding work hours, both moderate and intensive work was significantly related to substance use and status offenses, whereas only intensive work was significantly related to crime. The effects of intensive work on substance use and status offenses were different between male and female.